Tracking truth knowledge, evidence, and science - Roush, Sherrilyn; Oxford eBooks (Oxford : Clarendon, 2005)
Sherrilyn Roush defends a new theory of knowledge and evidence based on the idea of 'tracking' the truth as the best approach to a wide range of questions about knowledge-related phenomena. She explains why scepticism is frustrating and why knowledge is power.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Truth; Knowledge, Theory of; Evidence; Electronic books